Susceptibility Patterns and Factors Associated with Multidrug Antibiotic Resistance Among Patients with Productive Cough in Southwestern Uganda - Ezekiel W; Kegoye ES; Ssempijja F; Maniga JN; Ampeire IP; Abdi AA (Dove Medical Press, 2026)
Winnie Ezekiel,1 Eric Simidi Kegoye,2,3 Fred Ssempijja,4,5 Josephat Nyabayo Maniga,6 Isaac Petit Ampeire,1 Awil Abdulkadir Abdi1 1Department of Internal Medicine, Kampala International University Teaching Hospital, Bushenyi, Uganda; 2Department of Human Anatomy, Kenya Methodist University, Meru, Kenya; 3Department of Human Anatomy, Kampala International University, Bushenyi, Uganda; 4Infection Medicine, Edinburgh Medical School, Deanery of Biomedical Sciences, College of Medicine and Veterinary Medicine, The University of Edinburgh, Edinburgh, UK; 5School of Allied Health, St. Lawrence College, Kingston, Canada; 6Department of Microbiology and Immunology, Kampala International University, Bushenyi, UgandaCorrespondence: Awil Abdulkadir Abdi, Department of Internal Medicine, Kampala International University Teaching Hospital, Bushenyi, Uganda, Email awil6263@gmail.comBackground: Antibiotic resistance is a growing global public health concern, yet data on bacterial pathogens and susceptibility patterns among patients with productive cough in Uganda are scarce. This study aimed to determine the prevalence, bacterial isolates, susceptibility profiles, and factors associated with antibiotic resistance at Hoima Regional Referral Hospital, Uganda.Methods: A cross-sectional study was conducted among 216 adult outpatients presenting with productive cough. Sociodemographic, lifestyle, and medical data were obtained using structured questionnaires. Sputum samples were cultured, and antibiotic susceptibility testing was performed using Kirby-Bauer disk diffusion according to Clinical and Laboratory Standards Institute (CLSI) M100 (2022) guidelines. Logistic regression analyses were used to identify factors associated with antibiotic resistance. A p value of < 0.05 was considered statistically significant.Results: Bacterial pathogens were isolated in 139 (64.4%) patients. The most frequent were Streptococcus pneumoniae 57 (40.8%), Staphylococcus aureus 40 (28.6%), Klebsiella pneumoniae 17 (12.2%), and Streptococcus pyogenes 14 (10.2%). Most bacterial isolates were sensitive to imipenem 105 (75.5%), ceftazidime 92 (66.7%), and cefepime 81 (58.5%), while the lowest was to ampicillin 13 (9.5%) and amoxicillin 13 (9.5%). Antibiotic resistance was associated with smoking (aOR = 2.89, 95% CI: 1.074– 7.784, p = 0.036) and prior use of antibiotic (aOR = 2.65, 95% CI: 1.103– 6.369, p = 0.029).Conclusion: Among outpatients with a productive cough at Hoima Regional Referral Hospital, Streptococcus pneumoniae, Staphylococcus aureus were the leading Gram-positive isolates, and Klebsiella pneumoniae was the most common Gram-negative. Gram-negative isolates showed more susceptibility to ceftazidime, and overall susceptibility was more for imipenem, whereas ampicillin and amoxicillin demonstrated very low activity. Antibiotic resistance was significantly associated with smoking and prior use of antibiotic. These findings underscore the need for routine sputum culture and sensitivity testing, and strengthened public health measures to reduce smoking and inappropriate use of antibiotic.Keywords: multidrug resistance, productive cough, Streptococcus pneumoniae, Staphylococcus aureus, Klebsiella pneumoniae, use of antibiotic, smoking, Uganda
Keywords: multidrug resistance; productive cough; Streptococcus pneumoniae; Staphylococcus aureus; Klebsiella pneumoniae; use of antibiotic; smoking; Uganda